A relevância dos custos da qualidade para a gestão empresarial - Lopes, Luis Felipe (Revista Gestão da Produção Operações e Sistemas, 2006)
It was observed, in this paper, that most companies do not use or have enough knowledge about the costsgenerated by quality or bad quality. Therefore, this study aimed at introducing quality costs as a managerialtool in the central region of the state of Rio Grande do Sul, supplying data to the organizations, so that theycould know the matter, become interested and start to report quality costs as a form of quality control. Thus,one company, among those interested in controlling quality costs, was chosen for the application of a reportmodel. Noteworthy is that the company is in the early stage of control and that the process of measuring qualitycosts shall be reviewed in order to assure that quality costs are being corretly quantified.Keywords: Quality costs; Quality; ISO 9000.